Categories and Constraints in Causal Perception. (November 2017) - Kominsky, Jonathan F.; Strickland, Brent; Wertz, Annie E.; Elsner, Claudia; Wynn, Karen; Keil, Frank C.
When object A moves adjacent to a stationary object, B, and in that instant A stops moving and B starts moving, people irresistibly see this as an event in which A causes B to move. Real-world causal collisions are subject to Newtonian constraints on the relative speed of B following the collision, but here we show that perceptual constraints on the relative speed of B (which align imprecisely with Newtonian principles) define two categories of causal events in perception. Using performance-based tasks, we show that triggering events, in which B moves noticeably faster than A, are treated as being categorically different from launching events, in which B does not move noticeably faster than A, and that these categories are unique to causal events (Experiments 1 and 2). Furthermore, we show that 7- to 9-month-old infants are sensitive to this distinction, which suggests that this boundary may be an early-developing component of causal perception (Experiment 3).